ANALISIS KORELASI PERTUMBUHAN PENDUDUK DAN PERTUMBUHAN SARANA PRASARANA FASILITAS SOSIAL DI KECAMATAN KOTO TANGAH TAHUN 2014 DAN 2019 - THESYA WIDYA PUTRI; Afdhal Afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study discusses the Correlation Analysis of Population Growth and Growth of Social Infrastructure in Koto Tangah District in 2014 and 2019. Aims to determine the population growth rate in Koto Tangah District, the rate of additional social facilities in Koto Tangah District, the effect of population growth on the availability of infrastructure in the District. Koto Tangah. The research method uses descriptive quantitative research, secondary data analysis. The results showed the population growth rate in Koto Tangah District was 1.4% including the criteria for moderate growth rates, 184 educational facilities, 177 health facilities, 396 units of worship facilities, the effect of population growth on social infrastructure in 2014 educational facilities contributed 91, 8%, health facilities 89.7%, religious facilities 81%, in 2019 educational facilities 60.6%, health facilities 74.5%, worship facilities 83%. Key words: growth, facilities, infrastructure and social